Liberální teorie menšinových práv: Mýtus o neutralitě státu a etnokulturní spravedlnost - Muhič-Dizdarevič, Selma (Lidé města, 2005)
This article is a part of a wider work and it’s ambition is to undertake a journey through contemporary landscape of issues related to immigration problems. These problems have many pressing sides: they are challenging, both from the point of view of a current political agenda, as well as from the point of view of predominantly theoretical perspective. They involve questions like: what is a concrete society based on, is there such a basis, what is the meaning and justification of borders in a nowadays liberal state, is the immigration issue related to security and how, what is the meaning and value of nation-state concept, but also of the welfare state concept, why are some societies more open for multiculturalism than the others etc. But at the same time there is a strong debate from a purely theoretical point of view, namely from the perspective of liberal theory, involving also some basic issues describing current state of affairs within the liberal states as such. Here I have in mind the following: dominance of instrumental reason over all other powers of mind, civic privatism as its corresponding political reflection and social atomism on the level of individuals. The way I see it, these three points laid a basis for a strong self-understanding of the Western liberal societies, which affect heavily their relationship to outsiders, as well as the denizens. At the same time, I try to approach this question by restricting to one group and description of how liberal theory of minority rights, mainly in Kymlicka’s version, affect its meaning and position in the society. This group are immigrants. The group fits into general dynamics of majority/minority relationship, it is, however, especially interesting, because: 1. unlike national minority, it cannot claim the degree of autonomy stemming from participating in the national myth of a long presence on a certain territory and 2. unlike refugees or asylum seekers, it cannot rely on external state help to a significant degree. I am going to refer to them as denizens, because it seems that their most important feature in the functioning of society is exactly the lack of access to political life, due to the lack of citizenship.